Analysis of errors due to deficient mastery of prerequisite skills, facts and concepts: A case of financial mathematics - Khalo, Xolani; Bayaga, Anass (The IIE, 2015)
The main aim of the study was (1) to identify errors committed by learners in financial mathematics, and, (2) to understand why learners continue to make such errors so that mechanisms to avoid them could be devised. It has been hypothesised that errors committed by learners in financial mathematics are not due to a lack of prerequisite skills, facts and concepts. Using Newman’s Error Analysis as a theoretical framework,a four-point Likert scale and a content-based structured-interview questionnaire was developed to identify the errors committed. The study was conducted by means of a case study guided by the positivists’ paradigm where the research sample comprised of 105 Grade10 Mathematics Literacy learners as respondents. A structured-interview questionnaire was used for collecting data, aimed at addressing the main objective of the study. In order to test the reliability and consistency of the items in the questionnaire, Cronbach’s Alpha was calculated for standardised items (α = 0.705). Data analysis through content analysis and correlation analysis revealed that learners tend to forget to read the instructions (A) and rounding off incorrectly (C), was weakly significant, as p<.01 (r = +.31). The hypothesis was tested through Analysis of Variance (ANOVA) revealed that errors committed by learners in financial mathematics are not due to the lack of prerequisite skills, facts and concepts, as the variables showed non-significance.
Keywords: Mathematics; Mathematical Literacy; Financial Mathematics